Anaerobic co-digestion of food waste and septage in batch mode effect of mixture composition on biogas production and waste treatment performance - Delos Reyes, Rodelma B. (2012)
Food waste (FW) from food processing and food service industries are usually dumped in sanitary landfill, uncontrolled dumpsites or treated using aerobic composting methods. This study used anaerobic process, which has a potential for net energy recovery in the form of biogas, and determined the effect of co-digestion of FW with septage (S) on process performance. The effects of varying ratio of food waste to septage (FW:S = 100:0, 70:30, 50:50, 30:70, 0:100) to the rate of methane production and hydrolysis of solids, volatile solids (VS) removal and methane yield were determined. The rate of hydrolysis of solid or particulate substrate is described by a first order kinetic equation. The 30:70 FW:S mixture (100 g VS-FW:12 g VS-S) had the highest value of hydrolysis rate constant. The hydrolysis was fast during the first 5 days as indicated by the rapid decrease in pH. The latter signifies relatively high level of volatile fatty acid. Hydrolysis of the remaining VS was rate-limiting. The highest VS removal after 30 days digestion was 27.44% for the mixture without septage (100:0 FW:S). Co-digestion of FW with septage has significantly improved waste stabilization. as high as 263.57 L CH4/kg VSremoved was obtained from the mixture of 50:50 FW:S. The biogas contains as high as 82.36% methane (30:70 FW:S ratio, 48.37 COD/TKN ratio)